The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
HEM 2021
DOI: 10.21272/hem.2021.2-03
|View full text |Cite
|
Sign up to set email alerts
|

Motivation management model and practical realization within the health care institutions

Abstract: The motivation of medical workers is essential to society since the quality of their work affects the individual and public health. The authors highlighted the special role of state and municipal authorities in motivating medical professionals. The study aims to identify the main directions and elaborate the recommendations to build motivational management models in health care facilities. The study reveals the essence and objectives of personnel policy management in health care facilities. The main methods of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In establishing cooperation between teams, it is necessary to maintain so that every problem can be solved through evaluation, and discussion, even if the length of work is intertwined with cooperation, it will be a good work experience. It was also found that some nurses had a less visible performance from the obedience component, so nurses at work would be better if nurses took action according to SOP provisions and arrived on time according to working hours (Demirhan et al, 2020;Mamay et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In establishing cooperation between teams, it is necessary to maintain so that every problem can be solved through evaluation, and discussion, even if the length of work is intertwined with cooperation, it will be a good work experience. It was also found that some nurses had a less visible performance from the obedience component, so nurses at work would be better if nurses took action according to SOP provisions and arrived on time according to working hours (Demirhan et al, 2020;Mamay et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In carrying out the duties and responsibilities of nurses at work, nurses need psychological support from the leadership/head of the ward where they work (Mamay et al, 2021). This support greatly affects the level of performance, one of which is motivation.…”
Section: Introductionmentioning
confidence: 99%
“…The following recent publications are worth mentioning here Jakimowicz and Rzeczkowski (2019), Gerards et al (2020), Demircioglu and Chowdhury (2020). The way in which attributive characteristics of the internal business environment such as entrepreneurial motivation or risk acceptance is affected on enterprise development was studied extensively by Grabara et al, 2019; Rajan, 2019; Ik & Azeez, 2020; Kaya, 2020; Mamay et al., 2021.…”
Section: Identification Of Trends In Researchmentioning
confidence: 99%